Evaluation of functional properties of rice-dehulled mungbean flour - Joaquin, Lorena de Guzman; Galvez, Flor Crisanta F. (1999.)
The functional properties and nutritional qualities of nutritionally and economically important rice-dehulled mungbean flour were studied. The proportion used for the flour was 70:30 (rice to dehulled mungbean). Functional properties of the flour components were evaluated. Using the Kjeldahl Method in protein determination, rice flour, dehulled mungbean flour and rice-dehulled mungbean flour were found to have protein contents of 7%, 25% and 13% respectively. Other functional properties like water and fat absorption, viscosity, solubility, gelation, dough formation and bulk density were evaluated. The rice-dehulled mungbean flour had produced the following properties: water absorption = 225%; fat absorption = 195%; viscosity = 387.7 centipoise (spindle no. 2 is used; solubility = pH 8 to 14; gelation = 10-14% concentration; dough formation = negative; and bulk density = 0.68 g/ml.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Rice flour -- Evaluation; Mungbean flour -- Evaluation